Sulpiride and the potentiation of progestogen only contraception. Issue 6495 (31st August 1985) - Payne, M R; Howie, P W; McNeilly, A S; Cooper, W; Marnie, M; Kidd, L
Abstract : A progestogen (norethisterone) and a dopamine antagonist (sulpiride) were given alone and in combination to volunteers to examine their effects on excretion of ovarian steroids. Compared with non-treatment cycles (n = 15), contraception with a progestogen alone (n = 10) was associated with increased excretion of oestrone and partial suppression of excretion of pregnanediol, suggesting partial luteinization of unruptured follicles. By contrast, the combination of norethisterone and sulpiride (n = 9) suppressed both ovarian steroids to basal values, the suppression being even greater than with sulpiride alone (n = 5). These results suggest that a combination of a progestogen with a dopamine antagonist might have a role in contraception.